Photoptics 2014 : Proceedings of the 2nd International Conference on Photonics, Optics and Laser Technology ; revised selected papers /: Proceedings of the 2nd International Conference on Photonics, Optics and Laser Technology ; revised selected papers. (2016) - Unknown
No abstract available